ANALYSIS OF THE IMPLEMENTATION OF AREA ENTRY PERMITS (SIMA) IN AN EFFORT TO IMPROVE EMPLOYEE PERFORMANCE AT PERTAMINA EP CEPU'S JTB GAS DRILLING PROJECT - Hidayat, Ahmad; Paizal , Andi (International Peneliti Ekonomi, Sosial dan Teknologi, 2021)
Many work accidents are caused by undisciplined in the use of PPE (Personal Protective Equipment), not complying with standard procedures, and using the wrong machine and equipment. The purpose of this study is to analyze and evaluate SIMA implementation in the JTB-PEPC Gas drilling project, and using qualitative research methods with data collection techniques of observation, interviews, and documentation. The results of this study show that the SIMA implementation to improve employee performance in the JBT-PEPC Gas drilling project has been running Process by producing faster drilling times than the target and can reduce the number of work accidents, but in SIMA implementation there are still some findings that have not been maximized, because they are still found violations that can affect employee performance will cause work accidents and employee discipline is still low in the use of PPE.